The science of sampling: probability sampling techniques / Dr. Nur Izzah Jamil - Jamil, Nur Izzah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Ever wondered how random samples are chosen? Take a look at the techniques used in probability sampling! This method ensures that every individual in a population has an equal chance of being selected, leading to more reliable and unbiased results. From simple random sampling to structured approaches like stratified and cluster sampling, these techniques help researchers collect accurate data for studies, surveys, and experiments.